2023
DOI: 10.14503/thij-22-8055
|View full text |Cite
|
Sign up to set email alerts
|

Takotsubo Syndrome in Black Americans: Insights From the National Inpatient Sample

Olga Vriz,
Ali Hassan Mushtaq,
Ahmed Nahid Elshaer
et al.

Abstract: Background Data on race-related differences in the clinical outcomes of Takotsubo syndrome are limited, particularly for Black patients. This study aimed to assess whether race and sex may have an additional impact on the inpatient mortality of patients with Takotsubo syndrome. Methods A total of 4,628 patients from the United States' National Inpatient Sample from 2012 to 2016 were identified; propensity score analysis revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 35 publications
5
1
0
Order By: Relevance
“…This is consistent with the current literature that showed Black patients with TCM had higher rates of in-hospital adverse events and mortality [17]. The same study also found that inpatient mortality was higher for male patients who identified as Black than among females who identified as White [17]. While our study did not conduct an analysis on race and sex combined, on the basis of sex alone, our data found that females with TCM had lower mortality compared to males.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with the current literature that showed Black patients with TCM had higher rates of in-hospital adverse events and mortality [17]. The same study also found that inpatient mortality was higher for male patients who identified as Black than among females who identified as White [17]. While our study did not conduct an analysis on race and sex combined, on the basis of sex alone, our data found that females with TCM had lower mortality compared to males.…”
Section: Discussionsupporting
confidence: 92%
“…On the basis of demographics, our data showed that TCM patients who identified as Asian, Pacific Islander, or Black were at higher odds of mortality. This is consistent with the current literature that showed Black patients with TCM had higher rates of in-hospital adverse events and mortality [17]. The same study also found that inpatient mortality was higher for male patients who identified as Black than among females who identified as White [17].…”
Section: Discussionsupporting
confidence: 91%
“…In summary, it was noted that the Black population had more adverse outcomes compared to other races, which is consistent with literature 14 . The heightened presence of comorbidities among Black individuals may be elucidated by the disparities in the labor market and employment 15,16, which inadvertently expose them to more physically strenuous and hazardous occupations.…”
Section: Discussionsupporting
confidence: 90%
“…In summary, it was noted that the Black population had more adverse outcomes compared to other races, which is consistent with literature 15 .…”
Section: Discussionsupporting
confidence: 90%
“…This approach aimed to create matched cohorts with similar propensity scores between women with Turner syndrome and women without Turner syndrome. 18 , 19 …”
Section: Methodsmentioning
confidence: 99%